Reducing machining distortion in AA 6061 alloy through re-heating technique - Rafey Khan, Abdul; Nisar, Salman; Shah, A.; Khan, Muhammad A.; Khan, S. Z.; Sheikh, M. A. (Taylor & Francis, 2016)
Solution-treated AA 6061 alloy contains residual stresses which cause unwanted deformation during the machining operation rendering the parts unacceptable for use. Usually for AA 6061 alloy, stress relieving is performed by re-heating the parts at 343°C for 1 h. This stress relieving is however accompanied by a considerable loss of material strength which subsequently reduces the functionality of the parts. This paper is based on an effort to evaluate the effectiveness of lower re-heating temperatures for stress relieving without significant loss of strength. Temperatures within the range of 200–343°C were used and treated samples were tested for both the strength and machining distortion. The experimental results indicate 60% reduction in machining distortions with 21% decrease in the strength.
Keywords: AA 6061 alloy; Machining distortion; Residual stresses; Re-heating; Strength loss; Electron microscopy; Secondary precipitates; Mechanical properties